2023
DOI: 10.1002/adhm.202300054
|View full text |Cite
|
Sign up to set email alerts
|

A Metal‐Polyphenol‐Based Oxygen Economizer and Fenton Reaction Amplifier for Self‐Enhanced Synergistic Photothermal/Chemodynamic/Chemotherapy

Abstract: To overcome the limitations of doxorubicin (DOX) chemotherapy, nanomedicines that integrate additional photothermal therapy (PTT) and chemodynamic therapy (CDT) strategies are highlighted as promising alternatives for the treatment of malignant tumors. However, time-consuming preparation processes, biosafety concerns, and the bottlenecks of individual therapeutic modalities often limit the practical applications of this strategy. To address these issues, this work designs an oxygen economizer that additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Polyphenols such as TA, EGCG, and Gossypol have strong antioxidant activity and the ability to scavenge reactive oxygen species (ROS). As the ideal nanotherapeutic drug, MPCPs have broad application prospects [ 80 , 81 , 82 ]. For example, Li et al constructed a nanosystem for targeted cancer therapy based on Sm III -EC NPs [ 21 ].…”
Section: Biomedical Applications Of Mpcpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyphenols such as TA, EGCG, and Gossypol have strong antioxidant activity and the ability to scavenge reactive oxygen species (ROS). As the ideal nanotherapeutic drug, MPCPs have broad application prospects [ 80 , 81 , 82 ]. For example, Li et al constructed a nanosystem for targeted cancer therapy based on Sm III -EC NPs [ 21 ].…”
Section: Biomedical Applications Of Mpcpsmentioning
confidence: 99%
“…Usually, CDT was used to combinate with PTT and chemotherapy to achieve optimal tumor treatment. Shi et al designed a Fenton reaction amplifier through the assembly of EGCG, poloxamer F127, Fe 3+ , and DOX for the enhancement of synergistic PTT/CDT/chemotherapy [ 81 ]. The nanoplatforms inhibited cell respiration to reduce O 2 consumption, thus boosting H 2 O 2 generation for enhanced CDT and simultaneously improving DOX chemotherapy efficacy ( Figure 12 b).…”
Section: Biomedical Applications Of Mpcpsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that NIR irradiation of photothermal sensors increases local temperature, which improves molecular motion, accelerating the release of doping ions. [21,33] Thus, Ca, P, and Cu ions released from PC with NIR irradiation for 10 min at 0.5 W cm −2 (labeled as PC-L) were additionally measured (Figure 1g). After 1 day of immersion, the released ions of Ca, P, and Cu are 10.1, 23.8, and 5.37 ppm, respectively, which are slightly higher than those from PC without irradiation, and they are still in the positive concentration ranges for tissue regeneration or antibiosis.…”
Section: Microstructure and Characterizationmentioning
confidence: 99%